Effectiveness Test of the Antibacterial Activity of Endophytic Fungi RS-2 from Sambiloto (Andrographis paniculata) on Red Rice Media - Luqiyatur Rohmah; Suryelita Suryelita; Riga Riga; Mariam Ulfah (Indonesian Journal of Chemical Science and Technology (IJCST), 2023)
A. paniculata (Sambiloto) is a plant capable of producing various secondary metabolites which use in the field of pharmacology, one of which is as a source of antibacterial compounds. This potential can be explored from endophytic fungi associated with A. paniculata. The purpose was to determine the effectiveness of the antibacterial activity of the endophytic fungi RS-2 from branches of A. paniculata using red rice as the media. The stages of the research included isolation of the fungi, cultivation, extraction, antibacterial test, and test of the phytochemical of the endophytic fungi on branches of A. paniculata. The effectiveness test of antibacterial activity against the extract of the RS-2 endophytic fungi showed that the endophytic fungi extract had the potential to inhibit the growth of the three tested bacteria at concentrations of 10%, 30%, and 50%. The ethyl acetate extract of the endophytic fungi RS-2 from A. paniculata has the potential as a source of antibacterial compounds using red rice media.